Germination and initial development of Simira gardneriana seedling under water stress and at different temperatures - Fabrícia N. de Oliveira; Jessica R. de Oliveira; Salvador B. Torres; Rômulo M. O. de Freitas; Narjara W. Nogueira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The germination of seeds is affected by many factors, including water availability and temperature. This study aimed to evaluate the effects of water stress and different temperatures on germination and initial development of S. gardneriana M. R. Barbosa & Peixoto seedlings. The experiment was carried out in a completely randomized design, in a 7 x 4 factorial scheme, with seven potentials (0; -0.1; -0.2; -0.3; -0.4; -0.5 and - 0.6 MPa) and four temperatures (25, 30, 35 and 20-30 °C), with four replicates of 25 seeds. The analyzed variables were germination, percentage of normal seedlings, germination speed index, seedling length (shoot and root) and dry weight (shoot and root). There is a decrease in the germination and vigor of the seeds as the water potential decreases, being less affected under the temperature of 25 °C and very accelerated at 35 °C. The tolerance of S. gardneriana seed germination to water stress is variable between the temperatures and limiting to the formation of normal seedlings from the potential -0.5 MPa at temperatures of 25 to 30 °C and -0.4 and -0.2 MPa for 20-30 and 35 °C, respectively.